THE TEACHING OF COST ACCOUNTING. - Fiske, Wyman P. (The Accounting Review, 1944)
Cost accounting is fundamentally an analytical approach to the development of useful and necessary specialized management information. Techniques are only chosen methods of analysis and reports are a device to report results. Whether or not formal accounting routines and records are used is a matter of convenience and internal check. One of the first difficulties met in teaching cost accounting is the fact that there is not even a single fundamental definition or idea of cost which will meet all requirements. Cost has many different meanings, with only an extremely indefinite unifying idea to justify the application of the same term in such widely varying senses. The economist has long recognized this fact and carefully differentiates different meanings he attaches to the word. The basic business approach to cost was one of financial outlay. As developed by accountants, the businessman's primary idea of cost has been one of a normal average amount, determined as the sum of an accumulation of direct factory outlays and of a reasonable proration of indirect factory outlays. By outlay he means actual use or consumption of goods or services for which he has paid or is obligated to pay cash. The future of industrial cost analysis is bright, for it is a vitally essential business service. It has shown and can be expected to continue to show a rapid development in the quality of its service to industry. There is a need for better-trained juniors to enter cost accounting as a career.